Considering the κ − µ fading channels adopted in multiple antennas downlink non-orthogonal multiple access - Chi- Bao Le; Hong- Nhu Nguyen; Ngoc- Long Nguyen; Miroslav Voznak; Nhan Duc Nguyen (Bulletin of Electrical Engineering and Informatics, 2022)
Massive connectivity and effective spectrum usage have become more important as the use of wireless communication devices and networks has grown dramatically. The approach of non-orthogonal multiple access (NOMA) is advocated as a viable solution for meeting consumers’ current needs. The signals are overlaid with various power levels for each user in a NOMA-assisted system, and then broadcast to the receiver. SIC (successive interference cancellation) is used by the receiver to discriminate and get the needed signal. Until far, most studies have concentrated on SIC with ideal features, with only a handful focusing on SIC with imperfect qualities (ipSIC). While the perfect SIC (pSIC) represents the ideal condition of no data loss and no external sounds, the ipSIC represents data transfer in a real-time context. In this research, we will assess the system performance metrics of the investigated NOMA system in the presence of ipSIC and compare them to the performance of the same user’s pSIC. We define channels as κ−µ fading distributions, which is more essential. For two destinations, we construct accurate outage probability formulas. Meanwhile, Monte-Carlo simulations are run to ensure that the mathematical expressions derived are genuine.